2020
DOI: 10.15376/biores.16.1.583-596
|View full text |Cite
|
Sign up to set email alerts
|

Shear behavior of I-shaped wood-steel composite beam

Abstract: To expand the application of wood as a building material, a new type of I-shaped wood-steel beam that consisted of laminated veneer lumber and cold-formed thin-walled steel was considered in this paper. The shear performance of nine wood-steel composite beams was tested to evaluate the effects of shear span ratio, web thickness, and flange thickness. Then, the failure pattern and failure mechanism of the composite beams were analyzed. The main affecting factors of shear capacities were also discussed. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…By combining Hill's yield and element removal criteria, a new, high-fidelity finite element model was proposed. Wu et al [10] carried out the shear performance test on steel-wood composite beams, and established the calculation formula of shear capacity of composite beams according to the bending shear flow theory. Wang et al [11] performed four-point bending on a new type of I-LVL beam strengthened by cold-formed thin-walled channel steel, and found that considering the slip effect when calculating the flexural capacity was closer to the actual deformation than the section method.…”
Section: Introductionmentioning
confidence: 99%
“…By combining Hill's yield and element removal criteria, a new, high-fidelity finite element model was proposed. Wu et al [10] carried out the shear performance test on steel-wood composite beams, and established the calculation formula of shear capacity of composite beams according to the bending shear flow theory. Wang et al [11] performed four-point bending on a new type of I-LVL beam strengthened by cold-formed thin-walled channel steel, and found that considering the slip effect when calculating the flexural capacity was closer to the actual deformation than the section method.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai and Le (2018) reinforced the web of an I-shaped steel beam with timber using screws, and the strength of the composite beam was improved by about 15%. Wu et al (2021) developed an I-shaped wood-steel composite beam and reported that an elastic-plastic phase appeared as a result of the bending performance test. As mentioned above, researchers revealed the advantages of timber-steel composite beams.…”
Section: Introductionmentioning
confidence: 99%